Використання водневих паливних елементів для покриття балансу споживача електричної енергії - Андрєєв, А. Є. (Енергетика і автоматика, 2017)
UDC 621.311ANALYSIS OF ELECTRICITY CONSUMER’S USE OF HYDROGEN FUEL CELLSO. Andreyev Fuel cells - current power source based on the conversion of chemical energy to electrical energy. For stationary power greatest interest phosphate fuel cells, fuel cells with dissolved carbonate and solid oxide fuel cells. They are characterized by high operating temperatures and significant time to enter the nominal mode. Taking into account that fuel cells have a great term work and, as noted above, weak regulatory characteristics, you can use them to cover the base of the load.Pressing issue is analyzing the possibility of using fuel cells, depending on the operational characteristics of the consumer.The purpose of research - analysis of the possible use of hydrogen fuel cells for different groups of consumers of electricity.Materials and methods of research. In the first stage of solving problems it is necessary to study the formation of consumer groups, which may be offered different kinds of fuel cells.For the analysis of consumer groups that formed by the industry aspect, we used cluster analysis, because these methods often used to solve problems associated with higher levels of energy efficiency monitoring and analyzing energy efficiency.The purpose of the use of cluster analysis is the study of groups of electricity consumers by forming similar groups, which can identify potential load control through the use of alternative energy sources based on fuel cells and to form approaches to the use of certain types of fuel cells.To assess the ability of consumers to use fuel cells must take into account their multifaceted structure and specificity of each of its components.These indicators will identify groups of consumers with homogeneous nature of power consumption, for which you can select the appropriate fuel cell. Because fuel cells, which should be used as a large capacity power plants, have very little potential shunting and their proposed use to cover the base load, as part of a hybrid system formed for the consumer.Results. Clustering will implement the program STATISTIKA three methods: Association (tree clustering), clustering by K-averages, dvuvhodove association. Since the results for each of the methods are the same, the calculation results presented for clustering tree.After analyzing the results of clustering, decided to investigate for generalized indicator of electricity consumption to verify the results clustering.You can come to the conclusion that quite a large number of consumers have about the same index, the exception is only group Lighting and metallurgy. Thus, you can create 3 groups that are similar in composition to those obtained using cluster analysis.Considering the statistics, which conducted the study in terms of customer groups using mathematical and statistical methods can be divided consumers in terms of load regulation.ConclusionsThe results of the research fuel cells distributed among electricity consumers.It is proved that the use of the proposed approach to consumer research will effectively implement management practices power consumption based on modern alternative energy sources.To improve the efficiency of formation of consumer groups need to use additional indicators on reliability.